Stress disorders caused by quarantine during the COVID-19 pandemic - Palomino-Oré, Candy (2020)
The current COVID-19 pandemic has certain characteristics that could increase the levels of stress reaction in both the general population and health workers. People in quarantine are particularly vulnerable to neuropsychiatric complications due to gradual distancing, making disorders such as depression and anxiety more likely to appear. It is known that, in the context of other disasters, post-traumatic stress disorder (PTSD) occurred in up to 30–40 % of all affected people. This article aims is to carry out a narrative review of the stress consequences on mental health due to quarantine during past epidemics and pandemics, and during the current COVID-19 pandemic.